(untitled) (Kinesiology, 2022)
We aimed to investigate the relationships of isometric and eccentric shoulder abduction strength with acromiohumeral distance and supraspinatus tendon thickness based on the disease stage in patients with subacromial impingement syndrome. Eighty-two patients with subacromial impingement syndrome were assessed. Acromiohumeral distance and supraspinatus tendon thickness were measured using ultrasonography. Isometric and eccentric shoulder abduction strength were measured with a hand-held dynamometer. Spearman’s correlation coefficients were calculated. Isometric (rho = 0.428, p=.021) and eccentric (rho = 0.487, p=.007) shoulder abduction strength showed moderate correlations with acromiohumeral distance in patients with acute symptoms (n = 29). There was no relationship between acromiohumeral distance and abduction strength in patients with chronic symptoms (n = 53) (p>.050). Supraspinatus tendon thickness showed no significant correlation with abduction strength (p>.050). These findings suggest that the relationship between acromiohumeral distance and abduction strength differs according to disease stage. However, supraspinatus tendon thickness was not correlated with abduction strength regardless of disease stage. In patients with acute subacromial impingement syndrome symptoms increasing shoulder abduction strength may be a potential strategy to improve acromiohumeral distance. Key words: muscle strength, rotator cuff, rehabilitation, ultrasonography